Modernity, tradition and modernity in tradition in Muslim societies - Moten, Abdul Rashid (IIUM Press, 2011)
Modernity and tradition though considered to be the opposite of each other. It need not be so. In the Muslim countries, modernity and tradition supplement each other. Tradition has accommodated many modern elements and modernity has absorbed some of the principles dear to Islam.